2013
DOI: 10.3390/cancers5020418
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of the Combination of Temsirolimus with Irinotecan for Metastatic Sarcoma

Abstract: mTOR inhibitors are emerging as important anti-neoplastic agents with a wide range of clinical applications. The topoisomerase I inhibitor irinotecan is a potent DNA damaging drug, with a broad spectrum of anticancer activities. mTOR appears to enhance cancer cell survival following DNA damage, thus the inhibition of mTOR after irinotecan could theoretically show synergistic activities in patients. Both mTOR inhibitors and irinotecan have been used as single agents in soft tissue sarcomas with limited efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Although temsirolimus is well tolerated as a single agent, phase I combination studies including temsirolimus have frequently been found to have significant toxicities . Oral mucositis was the predominant toxicity in a pediatric phase I combination of temsirolimus with cixutumumab, resulting in two grade 3 mucositis DLTs and required two dose deescalations to achieve a RP2D (temsirolimus 8 mg/m 2 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although temsirolimus is well tolerated as a single agent, phase I combination studies including temsirolimus have frequently been found to have significant toxicities . Oral mucositis was the predominant toxicity in a pediatric phase I combination of temsirolimus with cixutumumab, resulting in two grade 3 mucositis DLTs and required two dose deescalations to achieve a RP2D (temsirolimus 8 mg/m 2 ) .…”
Section: Discussionmentioning
confidence: 99%
“…12 Although temsirolimus is well tolerated as a single agent, phase I combination studies including temsirolimus have frequently been found to have significant toxicities. [16][17][18][19][20][21][22] Oral mucositis was the predominant toxicity in a pediatric phase I combination of temsirolimus with cixutumumab, resulting in two grade 3 mucositis DLTs and required two dose deescalations to achieve a RP2D (temsirolimus 8 mg/m 2 ). 19 Significant oral mucositis and hypertriglyceridemia, accounting for four DLTS, occurred in a pediatric study of temsirolimus (15 mg/m 2 weekly) with vinorelbine and cyclophosphamide for rhabdomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The regimen irinotecan + temsirolimus was evaluated in adult patients with metastatic sarcoma, with disease stabilization observed in some patients (11%) [ 57 ]. DLTs included neutropenia, muscle weakness, platelet count decrease, and the recommended phase 2 dose (RP2D) was irinotecan 80 mg/m 2 + temsirolimus 20 mg on a weekly basis for 3 out of 4 weeks [ 57 ].…”
Section: Clinical Experience With Topoisomerase I Inhibitors In Sarcomasmentioning
confidence: 99%
“…Combination mTOR clinical trials have been or are being performed with multiple therapeutic partners. Regarding cytotoxics, liposomal doxorubicin , cyclophosphamide , irinotecan have all been attempted with modest results. In addition, there is an ongoing study with gemcitabine (NCT01684449).…”
Section: Targeting Cell Cyclementioning
confidence: 99%